Competency Strategies in Alleviating Poverty for Sustainable Development in the Teaching and Learning of Home Economics Education - Obasigie, I.O; Omoregbe, I.I (Mediterranean Journal of Social Sciences, 2012)
This study looked at poverty scenario in Edo State and how Home Economics graduate from theuniversities can use their competency to alleviate poverty for sustainable development. A self developedquestionnaire of 4 point instrument was used for data collection from150 respondents from 25 shops in 2zones i .e commercial and residential areas in Edo State. The data collected was subjected to frequencydistribution count and percentage rating analysis. The findings shows that majority of the home economicsgraduate from our universities exhibited low competencies of less than 15.0% in business managementfeasibility, business risk management, business finance management, and creativity ability in alleviatingpoverty in their chosen business ventures: the reasons being that they were all involved in buying andselling cake items for baking, interior decoration items, provision and toiletries among others. Findingsfurther revealed that all the studied respondents were highly constrained by lack of competency strategies;solutions were thus proffered and established for sustainable development.